Method for testing plugging property of artificial filter cake of nano-micron plugging agent
By using artificial filter cake to simulate formation microfissions, combined with indicators such as the reduction rate of permeability filtration loss, the evaluation problem of lack of unified standards in the existing technology is solved, and the accurate evaluation and mechanism research of the performance of nano-micron sealant is achieved.
Patent Information
- Application Number
- CN202311192188.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-15
AI Technical Summary
The prior art lacks a unified standard method to evaluate the sealing performance of nano-micron sealing agents, especially when simulating micro-cracks of mud shale formations, the data obtained are of poor objectivity and accuracy.
The artificial filter cake was used as the filter medium to prepare the filter cake by combining barite and polymer, simulate the formation microfission, and evaluate the performance of the nano-micron sealant through indicators such as the reduction rate of permeability filtration loss.
The intuitive and quantitative study of the performance of nano-micron sealant is achieved, providing an accurate and reliable evaluation method, which can effectively evaluate the sealing performance and mechanism of different sealant.
Smart Images

Figure CN119643399A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drilling engineering, and in particular to a method for testing the plugging performance of an artificial filter cake of a nano-micron plugging agent. Background Art
[0002] In drilling projects, wellbore instability is very likely to occur due to the development of micro-cracks and pores in shale formations. The excellent plugging performance of drilling fluid is an important basis for solving wellbore instability. Nanomaterials have small particle sizes and can enter micro-nano-scale cracks and pores for effective plugging, thus achieving the purpose of stabilizing the wellbore.
[0003] There has been no unified standard for the evaluation of nano-micro plugging agents. At present, the main methods for evaluating the plugging effect of nano-micro plugging agents and drilling fluid systems are as follows: Yue Qiansheng et al. used low-permeability artificial cores, sliced metal cores and oil-based drilling fluid filter cake permeabilities to characterize the plugging ability of single treatment agents and drilling fluid systems on microcracks in order to simulate microcracks in hard and brittle shale; Chen Liang used a homemade metal seam plate in conjunction with a high-temperature and high-pressure water loss instrument based on the characteristics of micro-fracture formations. Through the adjustment of rulers and screws, the iron block can simulate 20-100μm microcracks with a depth of 5mm and a rough surface inside the crack. After completion, the inside of the crack can be observed, which is simple and practical, and the simulation effect of microcracks is accurate; Yang Juesuan et al. used dry drilling to sample cores to obtain standard core columns, made seams in the core columns, and simulated microcracks of different widths (micrometer level) by using tin foil of different thicknesses on the core seam surface. Yan Jing used natural cores, metal foils of different thicknesses and cementitious materials to cast microcracks to simulate real pore throats and microcracks, and evaluated the plugging performance of plugging agents. The minimum width of the simulated core cracks was 3.33μm, the stroke was 5-10cm, and the repetition rate was high. These methods are direct simulations of rock cracks, and have a certain guiding role in evaluating the plugging effects of nano-micro plugging agents and drilling fluids, but there are problems such as poor repeatability and the inability to deeply analyze and study the plugging agent mechanism from a microscopic perspective.
[0004] Through the above analysis, the problems and defects of the prior art are as follows:
[0005] There is no standard method for evaluating the plugging performance of plugging agents. Due to the low permeability and small pores of shale formations, there is no dedicated medium to simulate them. Therefore, the plugging performance data of plugging agents obtained by existing technologies are less objective and accurate. Summary of the invention
[0006] The purpose of the present invention is to provide a method for testing the plugging properties of an artificial filter cake of a nano-micron plugging agent, to carry out research on an evaluation method and action mechanism of a nano-micron plugging agent, to preferably determine an evaluation method of a nano-micron plugging agent, to systematically evaluate the nano-micron plugging agent based on this, and to clarify the action mechanism of the nano-micron plugging agent by combining instrument testing and theoretical analysis.
[0007] The technical solution adopted by the present invention to achieve its invention object is to provide a method for testing the plugging performance of an artificial filter cake of a nano-micro plugging agent, the steps of which are as follows:
[0008] S1. Pour a portion of the evenly stirred filter cake slurry into the drilling fluid cup of the high temperature and high pressure filter loss instrument, and obtain the initial filter cake after filtering and dehydration for two hours at room temperature and 3.45 MPa pressure;
[0009] S2, add 100 mL of distilled water into the drilling fluid cup containing the initial filter cake using a glass rod, measure the filtration loss L1 at room temperature and 3.45 MPa pressure for 30 min, and then pour out the remaining distilled water;
[0010] S3, weigh 20g of nano-micro plugging agent sample and add it to a beaker containing 180mL of distilled water or white oil, place it in an ultrasonic disperser and disperse it for 15min to obtain a sample solution, then drain the sample solution with a glass rod and add it into the drilling fluid cup containing the initial filter cake to obtain a filter cake with nano-micro plugging agent added, and measure its filtration loss L2 under room temperature and 3.45Mpa pressure conditions for 30min; if L2≥L1, discard the filter cake with nano-micro plugging agent added, repeat step S1, if L2<L1, first pour out the remaining sample solution, and then go to step S4;
[0011] S4, add 100 mL of distilled water into the drilling fluid cup containing the filter cake of the nano-micro plugging agent by drainage with a glass rod, and measure the filtration loss L3 under the conditions of room temperature and 3.45 MPa pressure for 30 minutes;
[0012] S5. Evaluate the plugging performance of the nano-micro plugging agent on the artificial filter cake by the permeability loss reduction rate P. The permeability loss reduction rate P is calculated by the formula:
[0013]
[0014] Where:
[0015] L1 is the clean water permeability loss of the initial filter cake, in mL; L3 is the clean water permeability loss of the filter cake with nano-micro plugging agent added, in mL.
[0016] Furthermore, in step S1, after obtaining the initial filter cake, it is necessary to take out the initial filter cake in the drilling fluid cup, blow the filter cake with a hot air blower for 20 seconds, measure its thickness l, and then put it back into the drilling fluid cup; in step S5, it is necessary to evaluate the plugging performance of the initial filter cake by the average permeability K, and the average permeability K (unit is 10 2 mD) is calculated as:
[0017]
[0018] Where:
[0019] q is the volume of distilled water lost per unit time, in cm 3 / s; l is the filter cake thickness, in cm; μ is the viscosity of distilled water at room temperature, in mPa·s; A is the filter cake area, in cm 2 ; △p is the experimental pressure difference, the unit is MPa;
[0020] Wherein: μ is the viscosity of distilled water at 25°C, 0.8937 mPa·s; the experimental pressure difference △p is 3.45 MPa.
[0021] Furthermore, the filter cake slurry in step S1 is a uniform suspension formed by adding ordinary barite and nano-barite to polyacrylamide and sodium polyacrylate solution and dispersing them.
[0022] Furthermore, the specific preparation method of the filter cake base slurry is: first, polyacrylamide and sodium polyacrylate are added to water according to a set mass ratio and stirred for one hour to completely dissolve them; then, composite barite compounded by ordinary barite and nano-baryte is added during stirring, and stirred for 30 minutes to mix them evenly.
[0023] Furthermore, the mass ratio of the raw materials of the filter cake base slurry is ordinary barite: nano barite: water: polyacrylamide: sodium polyacrylate = 250:100:1000:3:9.
[0024] Furthermore, the median particle size of the common barite is 200 μm, and the median particle size of the nano-baryte is 0.89 μm.
[0025] Furthermore, the nano-micron plugging agent is ultrafine calcium carbonate, or emulsified modified rubber MORLF, or ULIA nano pressure-bearing plugging agent.
[0026] Furthermore, the filter cake thickness l is measured using a needle-type thickness gauge.
[0027] The beneficial effects of the present invention are:
[0028] The present invention uses artificial filter cakes that simulate microcracks in shale formations as filter media, and evaluates the performance of nano-micro plugging agents by the reduction rate of permeability loss. This evaluation method uses compound barite and high molecular polymer to prepare filter cakes, simulates microcracks in formations, and selectively selects nano-micro plugging agents that match the formations, realizing an organic combination of intuitive and quantitative research.
[0029] The present invention evaluates the plugging performance of three plugging agents with greatly different particle sizes (ultrafine CaCO3, emulsified modified rubber MORLF, ULIA nano pressure-bearing plugging agent), verifies the accuracy of the evaluation method, and conducts a simple analysis of their plugging mechanisms.
[0030] The thickness of the artificial filter cake of the present invention is stable at about 3 mm, and the permeability is stable at 10 -3 ~10 -4 Within the mD range, the evaluation method has parallelism and accuracy, and can be used as a guiding method for evaluating nano-micron plugging agents.
[0031] The technical solution of the present invention solves the technical problem that the plugging materials for oil-based drilling fluids in the petroleum industry have always been unable to be evaluated simply, conveniently and effectively. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 is a graph showing the reduction rate of filter cake permeability loss after adding different nano-micron plugging agents in an embodiment of the present invention;
[0033] Figure 2 It is the initial filter pie chart of the embodiment of the present invention;
[0034] Figure 3 This is a filter cake diagram after adding ultrafine calcium carbonate plugging agent in Example 1 of the present invention;
[0035] Figure 4 This is a filter cake diagram after adding the emulsified modified rubber MORLF plugging agent in Example 2 of the present invention;
[0036] Figure 5 This is a filter cake diagram after adding ULIA nano pressure-bearing plugging agent to Example 3 of the present invention. DETAILED DESCRIPTION
[0037] In order to more clearly understand the above-mentioned objects, features and advantages of the present invention, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0038] Example 1
[0039] The first specific implementation of the present invention is to use the method for testing the plugging performance of the artificial filter cake of the nano-micro plugging agent of the present invention, comprising the following steps:
[0040] S1. Pour a portion of the evenly stirred filter cake slurry into the drilling fluid cup of the high temperature and high pressure filter loss tester, and obtain the initial filter cake after filtering and water loss for two hours at room temperature and 3.45 MPa pressure. Take out the initial filter cake in the drilling fluid cup, blow the filter cake with a hot air blower for 20 seconds, measure its thickness l with a needle-type thickness gauge, and then put it back into the drilling fluid cup.
[0041] S2, add 100 mL of distilled water into the drilling fluid cup containing the initial filter cake using a glass rod, measure the filtration loss L1 at room temperature and 3.45 MPa pressure for 30 min, and then pour out the remaining distilled water;
[0042] S3, weigh 20g of nano-micro plugging agent sample and add it to a beaker containing 180mL of distilled water or white oil, place it in an ultrasonic disperser and disperse it for 15min to obtain a sample solution, then drain the sample solution with a glass rod and add it into the drilling fluid cup containing the initial filter cake to obtain a filter cake with nano-micro plugging agent added, and measure its filtration loss L2 under room temperature and 3.45Mpa pressure conditions for 30min; if L2≥L1, discard the filter cake with nano-micro plugging agent added, repeat step S1, if L2<L1, first pour out the remaining sample solution, and then go to step S4;
[0043] S4, add 100 mL of distilled water into the drilling fluid cup containing the filter cake of the nano-micro plugging agent by drainage with a glass rod, and measure the filtration loss L3 under the conditions of room temperature and 3.45 MPa pressure for 30 minutes;
[0044] S5. Evaluate the plugging performance of the nano-micro plugging agent on the artificial filter cake by the permeability loss reduction rate P. The permeability loss reduction rate P is calculated by the formula:
[0045]
[0046] Where:
[0047] L1 is the clean water permeability loss of the initial filter cake, in mL; L3 is the clean water permeability loss of the filter cake with nano-micro plugging agent added, in mL.
[0048] The plugging performance of the initial filter cake needs to be evaluated by the average permeability K, where the average permeability K (unit: 10 2 mD) is calculated as:
[0049]
[0050] Where:
[0051] q is the volume of distilled water lost per unit time, in cm 3 / s; l is the filter cake thickness, in cm; μ is the viscosity of distilled water at room temperature, in mPa·s; A is the filter cake area, in cm 2 ; △p is the experimental pressure difference, the unit is MPa;
[0052] Wherein: μ is the viscosity of distilled water at 25°C, 0.8937 mPa·s; the experimental pressure difference △p is 3.45 MPa.
[0053] In this embodiment, the filter cake base slurry is a uniform suspension formed by mixing ordinary barite and nano barite and adding them into polyacrylamide and sodium polyacrylate solution to disperse them.
[0054] The specific preparation method of the filter cake base slurry is: first, add polyacrylamide and sodium polyacrylate into water according to the set mass ratio and stir for one hour to completely dissolve them; then, add the composite barite compounded by ordinary barite and nano barite during stirring, and stir for 30 minutes to mix them evenly.
[0055] The mass ratio of each raw material of the filter cake base slurry is: ordinary barite: nano barite: water: polyacrylamide: sodium polyacrylate = 250:100:1000:3:9.
[0056] The median particle size of the common barite is 200 μm, and the median particle size of the nano-baryte is 0.89 μm.
[0057] In this embodiment, the nano-micron plugging agent is ultrafine calcium carbonate, the median particle size of which is 38150 nm.
[0058] Filter cake base slurry formula selection:
[0059] In order to produce an "artificial core" that can simulate the nano and nano-micro pores of the strata and has reproducible properties, it was determined through multiple experimental studies that a mixture of ordinary barite (200 μm) and nano-baryte (0.89 μm) was added to a high molecular polymer solution, which was dispersed into a uniform suspension and compacted into a filter cake of a fixed size under a high pressure difference. The filter cake can simulate the nano and nano-micro pores of the strata and can serve as a reproducible simulated "artificial core".
[0060] The mass ratio of the raw materials in Experiment 1# is ordinary barite: nanobarite: water: polyacrylamide: sodium polyacrylate = 1000:100:1000:3:9.
[0061] The mass ratio of the raw materials in Experiment 2# is ordinary barite: nanobarite: water: polyacrylamide: sodium polyacrylate = 500:100:1000:3:9.
[0062] The mass ratio of the raw materials in Experiment 3# is ordinary barite: nanobarite: water: polyacrylamide: sodium polyacrylate = 333:100:1000:3:9.
[0063] The mass ratio of the raw materials in Experiment 4# is ordinary barite: nanobarite: water: polyacrylamide: sodium polyacrylate = 250:100:1000:3:9.
[0064] Table 1 Initial filter cake performance under different compound barite conditions
[0065]
[0066] According to the experimental results, it was determined that the filter cake simulation artificial core used the recipe of experiment 4#, and its permeability was 10 -3 ~10 -4 mD.
[0067] Quasi-parallel analysis of test methods:
[0068] The permeability and thickness of the artificial filter cake were tested in parallel. The experimental results are shown in Table 2. The results of 10 repeated experiments were stable. The water loss in the clean water test was stable between 2 and 2.5 mL. The thickness of the artificial filter cake was about 3 mm, and the permeability was kept at 10. -3 ~10 -4 Within the mD range, it can be seen that the fluctuation of each group of data is very small, which proves that the artificial filter cake prepared by this experimental method has good parallelism and stability.
[0069] Table 2 Filter cake properties of parallel experiment
[0070]
[0071] Evaluation of the plugging performance of nano-micron plugging agents on artificial filter cakes:
[0072] like Figure 1 As shown, in this embodiment, after adding the ultrafine calcium carbonate plugging agent, the permeability loss reduction rate P is 41.7% to 45.5%.
[0073] Example 2
[0074] The second specific implementation mode of the present invention has the same steps as those of Example 1, except that the nano-micro plugging agent is emulsified modified rubber MORLF, and the median particle size thereof is 584 nm.
[0075] Evaluation of the plugging performance of nano-micron plugging agents on artificial filter cakes:
[0076] like Figure 1 As shown, in this embodiment, after adding the emulsified modified rubber MORLF plugging agent, the permeability loss reduction rate P is 50% to 55.6%.
[0077] Example 3
[0078] The third specific implementation mode of the present invention has the same steps as those of Example 1, except that the nano-micron plugging agent is a ULIA nano-pressure plugging agent, the average particle size of which is 2442 nm.
[0079] Evaluation of the plugging performance of nano-micron plugging agents on artificial filter cakes:
[0080] like Figure 1 As shown, in this embodiment, after adding ULIA nano pressure-bearing plugging agent, the permeability loss reduction rate P is 40% to 42.9%.
[0081] By analyzing and summarizing three examples:
[0082] like Figure 1 As shown, the emulsion-modified rubber MORLF with the smallest average particle size has the highest permeability loss reduction rate and the best plugging performance compared with the other two plugging agents.
[0083] like Figures 2 to 5 As shown in the figure, the filter cake after plugging with the emulsified modified rubber MORLF is obviously more uniform than the other two, forming a black waxy plugging layer on the filter cake surface, while the macroscopic changes of the filter cake surface before and after plugging with the ultrafine calcium carbonate and ULIA nano-pressure plugging agents are not significant. This shows that this experimental method can accurately evaluate the performance of nano-micro plugging agents.
[0084] In addition, through many experiments, it was found that the particle size composition of single barite is single, the range is narrow, the filter cake quality is poor, and the more concentrated the particle size distribution, the worse the filter cake quality; the particle size distribution of compound barite is wider, the filling effect of small particles is obvious, and the quality of the obtained filter cake is much better than that of single type of barite. Among the various groups of compound barite, when ordinary barite and nano-barite are compounded in a ratio of 250:100, the obtained packing density is the highest and the filter cake quality is the best. The artificial filter cake prepared using this ratio of compound barite as the filter medium has a stable thickness of 3mm and a stable permeability of 10 -3 ~10 -4 Within the mD range, the test results have good parallelism.
[0085] The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Although the present invention has been described in detail in this specification with reference to the above embodiments, the present invention is not limited to the above specific implementation modes. Therefore, any modification or equivalent replacement of the present invention and all technical solutions and improvements that do not depart from the spirit and scope of the invention are all covered by the scope of the claims of the present invention.
Claims
1. A method for testing the plugging performance of a nano-micron plugging agent artificial filter cake, characterized in that: The method comprises the following steps: S1. Pour a portion of the evenly stirred filter cake slurry into the drilling fluid cup of the high temperature and high pressure filter loss instrument, and obtain the initial filter cake after filtering and dehydration for two hours at room temperature and 3.45 MPa pressure; S2, add 100 mL of distilled water into the drilling fluid cup containing the initial filter cake using a glass rod, measure the filtration loss L1 at room temperature and 3.45 MPa pressure for 30 min, and then pour out the remaining distilled water; S3, weigh 20g of nano-micro plugging agent sample and add it to a beaker containing 180mL of distilled water or white oil, place it in an ultrasonic disperser and disperse it for 15min to obtain a sample solution, then drain the sample solution with a glass rod and add it into the drilling fluid cup containing the initial filter cake to obtain a filter cake with nano-micro plugging agent added, and measure its filtration loss L2 under room temperature and 3.45Mpa pressure conditions for 30min; if L2≥L1, discard the filter cake with nano-micro plugging agent added, repeat step S1, if L2<L1, first pour out the remaining sample solution, and then go to step S4; S4, add 100 mL of distilled water into the drilling fluid cup containing the filter cake of the nano-micro plugging agent by drainage with a glass rod, and measure the filtration loss L3 under the conditions of room temperature and 3.45 MPa pressure for 30 minutes; S5. Evaluate the plugging performance of the nano-micro plugging agent on the artificial filter cake by the permeability loss reduction rate P. The permeability loss reduction rate P is calculated by the formula: Where: L1 is the clean water permeability loss of the initial filter cake, in mL; L3 is the clean water permeability loss of the filter cake with nano-micro plugging agent added, in mL.
2. The method for testing the plugging performance of a nano-micron plugging agent artificial filter cake according to claim 1, characterized in that: In step S1, after obtaining the initial filter cake, it is necessary to take out the initial filter cake in the drilling fluid cup, blow the filter cake with a hot air blower for 20 seconds, measure its thickness l, and then put it back into the drilling fluid cup; in step S5, it is necessary to evaluate the plugging performance of the initial filter cake by the average permeability K, and the average permeability K (unit is 10 2 mD) is calculated as: Where: q is the volume of distilled water lost per unit time, in cm 3 / s; l is the filter cake thickness, in cm; μ is the viscosity of distilled water at room temperature, in mPa·s; A is the filter cake area, in cm 2 ; △p is the experimental pressure difference, the unit is MPa; Wherein: μ is the viscosity of distilled water at 25°C, 0.8937 mPa·s; the experimental pressure difference △p is 3.45 MPa.
3. A method for testing the plugging performance of a nano-micron plugging agent artificial filter cake according to claim 1 or 2, characterized in that: The filter cake slurry in step S1 is a uniform suspension formed by adding ordinary barite and nano barite into polyacrylamide and sodium polyacrylate solution and dispersing them.
4. The method for testing the plugging performance of a nano-micron plugging agent artificial filter cake according to claim 3, characterized in that: The specific preparation method of the filter cake base slurry is: first, polyacrylamide and sodium polyacrylate are added into water according to a set mass ratio and stirred for one hour to completely dissolve them; then, composite barite compounded by ordinary barite and nano barite is added during stirring, and stirred for 30 minutes to mix them evenly.
5. A method for testing the plugging performance of a nano-micron plugging agent artificial filter cake according to claim 4, characterized in that: The mass ratio of the raw materials of the filter cake base slurry is: ordinary barite: nanobarite: water: polyacrylamide: sodium polyacrylate = 250:100:1000:3:
9.
6. A method for testing the plugging performance of a nano-micron plugging agent artificial filter cake according to claim 4, characterized in that: The median particle size of the common barite is 200 μm, and the median particle size of the nano-baryte is 0.89 μm.
7. A method for testing the plugging performance of a nano-micron plugging agent artificial filter cake according to claim 1 or 2, characterized in that: The nano-micron plugging agent is ultrafine calcium carbonate, or emulsified modified rubber MORLF, or ULIA nano pressure-bearing plugging agent.
8. The method for testing the plugging performance of a nano-micron plugging agent artificial filter cake according to claim 2, characterized in that: The filter cake thickness l is measured using a needle-type thickness gauge.
Citation Information
Patent Citations
Evaluation mud cake for shale water-based drilling fluid blocking performance and preparation method
CN105866339A
Method for simulating microcrack of shale by using mud cake
CN106769301A
Indoor evaluation method for nano-plugging agent for shale gas water-based drilling fluid
CN109520897A
Method for evaluating plugging effect of nano-particles for drilling fluid
CN110082271A
Nano blocking agent as well as preparation method and application thereof
CN112430455A